Properties of Cold-Bonded and Sintered Aggregate Using Washing Aggregate Sludge and Their Incorporation in Concrete: A Promising Material - Ozkan, Hakan; Kabay, Nihat; Miyan, Nausad (MDPI, 2022)
The aggregate makes up about 65-75% of the total volume of concrete and the use of artificial aggregates manufactured from waste and by-product materials, as an alternative to natural aggregate, has attracted considerable research interest. Washing aggregate sludge (WAS) is obtained as a waste during the process of washing the aggregates, which is disposed or used as landfill. The utilization of WAS as a major component to manufacture artificial aggregates remains unexplored. Therefore, the focus has been directed towards the production of cold-bonded and sintered aggregates using WAS and their incorporation in concrete. The fresh pellets were manufactured using WAS, ground granulated blast furnace slag (GGBFS) and ordinary Portland cement (OPC) and kept in the laboratory conditions at 20 +/- 2 degrees C and 95 +/- 5% relative humidity to obtain cold-bonded aggregates, whereas WAS and GGBFS were utilized to manufacture sintered aggregate by heating the fresh pellets up to 1150 degrees C. The manufactured aggregate properties were characterized through physical, mechanical, chemical, and microstructural analysis. Concrete specimens were also produced by introducing the artificial aggregates in replacement with the coarse aggregate. The results showed that the concrete containing artificial aggregates can be produced with lower oven-dry density and comparable mechanical properties to efficiently utilize WAS.
Keywords: washing aggregate sludge; cold-bonded aggregate; sintered aggregate; concrete; compressive strength; LIGHTWEIGHT AGGREGATE; SEWAGE-SLUDGE; ASH; PERFORMANCE; DURABILITY; Science & Technology - Other Topics; Environmental Sciences & Ecology